The Impact of Diabetic Foot Ulcer on Health Related Quality Of Life and Employment among Diabetics Attending Tertiary Care Teaching Hospital, Davangere - Lekha Tejaswi Y; Navinkumar Angadi (Medsci Publications, 2018)
Background: Diabetic foot ulcer is the most common complication of diabetes mellitus. Diabetic foot disease reduces quality of life. It is associated with early retirement and reduced productivity. This research was conducted to study the health related quality of life among patients with diabetic foot ulcer; and also to study the im- pact of diabetic foot ulcer on employment status. Materials and Methods: This was a hospital based cross-sectional study. This study was conducted among 80 patients with diabetic foot ulcer attending the outpatient department of tertiary care teaching hospital Davangere. Results: Among 80 patients with diabetic foot ulcer, 79% had poor environmental domain composite score, 46% of the participants had poor physical and 48% had poor social health composite score. 38% study participants were not currently working. 15% had changed the job /wok they did because of their diabetic foot ulcer. Conclusions: Majority of patients with diabetic foot ulcer had poor health related quality of life and almost one-thirds of them were unemployed